Functional Modification and Applications of Rice Starch Emulsion Systems Based on Interfacial Engineering - Pingyuan Ge; Ye Tian; Heng Yan; Qingqing Li; Tianle Yao; Jie Yao; Liuyu Xiao; Meng Zhu; Yu Han (Foods)
Rice starch, as one of the most abundant and renewable polysaccharide resources in nature, holds great potential for applications in the food, pharmaceutical, and industrial fields due to its wide availability, low cost, and biodegradability. However, its inherent limitations—such as susceptibility to retrogradation and poor emulsifying capacity—have hindered its development into high-value-added products. Emulsion technology presents a promising strategy to overcome these challenges by constructing stable oil–water interfacial systems using various stabilizers. This review highlights recent advances in the functional modification of rice starch through emulsion-based techniques, with a particular focus on four key approaches: polysaccharide–protein complexation, chemical and physical modifications, Pickering emulsions, and microcapsule formation. These strategies significantly improve the emulsifying ability of rice starch, inhibit retrogradation, and expand its potential applications in sustained drug delivery, functional foods, and intelligent packaging. Overall, interfacial engineering of rice starch offers an innovative and effective pathway for its high-value utilization, demonstrating substantial promise for future industrial applications.